PENINGKATAN HASIL BELAJAR PKn MENGGUNAKAN PENDEKATAN KOOPERATIF TIPE JIGSAW DI SD - SOTIFA, OSRIZA (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This study originated from the fact that in school learning undertaken by teachers is still conventional, teacher-centered learning still. Therefore, the researchers in this study used a model of cooperative learning approach Jigsaw type). This study aims to improve the learning process in the fourth grade Civics District 40 District Lubuk cone Surabayo Agam District. This research is action research (Classromm action research), this study used qualitative and quantitative approaches undertaken by 2 cycles collaboratively between researchers and teachers. The research data in the form of information about the process and outcome measures obtained from the observation and recording of every action in Civics learning about the system of the central government in the fourth grade Surabayo District 40 District Lubuk cone Agam District, subjects were teachers and students of the fourth grade terteliti. Kata Kunci : hasil belajar, PKn, cooperatif learning tipe jigsaw